Tinjauan sarana dan prasarana pembelajaran pendidikan jasmani pada Sd Negeri di Kelurahan Batursari Kecamatan Mranggen Kabupaten Demak - Beni Apriawan; Husnul Hadi; Asep Ardiyanto (Journal of Physical Activity and Sports (JPAS), 2021)
Physical education facilities and infrastructure is one of the elements supporting the success of physical education learning. The need for physical education learning facilities and infrastructure is very vital, meaning that physical education must use facilities and infrastructure according to needs. In fact, it was found that physical education learning facilities and infrastructure were adequate and tended to be lacking. Physical education facilities are media or teaching aids in physical education. The infrastructure itself is divided into two, namely infrastructure or tools and infrastructure or facilities. Ideally, this tool should not be moved so that it is not easily damaged unless the space is limited so it must always be disassembled. Then infrastructure or facilities are everything that is needed in physical education learning, is permanent or cannot be moved. The research used in this research is survey research. This research does not test hypotheses or does not use hypotheses, but only describes what information is in accordance with the variables studied. The subjects in this study were SD Negeri 1-7 in Batursari Village, Mranggen District, Demak Regency. The results of the calculation explain that the total number, condition and ownership of facilities and infrastructure is SD N 1 Batursari is a school that totals all of the number, condition and ownership of facilities and infrastructure in the high category compared to other schools. Schools in the medium category are SD N 2 Batursari, SD N 5 Batursari, SD N 6 Batursari and SD N 7 Batursari. Schools in the low category are SD N 3 Batursari and SD N 4 Batursari. Based on the results of research and data on physical education facilities and infrastructure in State Elementary Schools in Batursari Village, Mranggen District, Demak Regency, only a small part of the physical education facilities and infrastructure owned by each school, most of the facilities and infrastructure are still in good condition and ownership status of all facilities and infrastructure are their own.